Angioplasty and stenting for symptomatic stenosis of the left subclavian artery complicated with aortic dissection. Issue 3 (3rd March 2021) - Huang, Chun-Chao; Huang, Wei-Ming; Jhou, Zong-Yi; Chen, Jung-Hsuan; Chen, Shu-Ting; Lin, Hui-Chen; Huang, Chung-Yao; Chen, Chia-Hung; Luo, Chao-Bao; Chang, Feng-Chi
Abstract : Background: Aortic dissection is a rare but severe complication of percutaneous transluminal angioplasty and stenting (PTAS) for stenosis of the subclavian artery (SA). This retrospective study was designed to evaluate the risk factors and outcomes of patients with severe stenosis of the SA who underwent PTAS complicated by aortic dissection. Methods: Between 1999 and 2018, 169 cases of severe symptomatic stenosis of the SA underwent PTAS at our institute. Of them, six cases complicated by aortic dissection were included in this study. We evaluated the demographic features, technical factors of PTAS, and clinical outcomes in these six patients. Results: Aortic dissection occurred in 5.3% (6/113) of all left SA stenting cases but in none of the right SA stenting cases. All patients had hypertension and a high severity of SA stenosis (85.0 ± 13.0%, 60%–95%). Five of the six patients received balloon-expandable stents (83.3%). All patients had spontaneous resolution of the aortic dissection with conservative treatment. In a 63.33 ± 33.07 (7–118) month follow-up, five of the six patients (83.3%) had long-term symptom relief and stent patency. Conclusion: Aortic dissection occurred in patients who underwent PTAS for severe stenosis of the left SA, mainly with balloon-expandable stents. We suggest using self-expandable stents and angioplasty with an undersized balloon during PTAS for severe stenosis of the left proximal SA to prevent aortic dissection.